Pemanfaatan Media Berbasis Teknologi Informasi Dan Komunikasi Di SMA Negeri 1 Sorkam Barat Kecamatan Sorkam Barat Kabupaten Tapanuli Tengah - Rosa Simamora; Tuti Anjelina Hasibuan; Mitry Ady Manalu; Jumanta Ferayanti Hasibuan; Arjuna Saruksuk; Ida Sopia Pandiangan (Program Studi Pendidikan Biologi, 2022)
Learning media is a means of channeling learning messages and information. Learning media that are well designed really help students digest and understand the subject matter. The development of information technology in globalization and current information has spurred the development of learning media to be even more advanced. The use of Information and Communication Technology (ICT) as a learning medium is already a requirement. Although the design of ICT-based media requires special expertise, it does not mean that the media is avoided and abandoned. ICT-based learning media can be in the form of internet, intranet, mobile phone, and CD Room/Flash Disk. This study uses a qualitative approach with a descriptive model to analyze and explain how information and communication technology is utilized in learning at SMA Negeri 1 Sorkam. Based on the research conducted, it can be said that the teacher's paradigm when utilizing information and communication technology in learning is still limited to the use of ICT-based computer media as presentation material in the learning process. The use of the internet is still limited to finding information about the material to be delivered, not used as a new integrated learning system, as well as social networks that are still not widely used as a new learning system to further increase the effectiveness and efficiency of the learning process.